The Effect of Articulate Storyline 3 Media on Fifth-Grade Elementary School Students' Interest in Learning English - Andini Andini; Leny Saili Rahmah; Wahyu Satya Gumelar (Journal of Educational Sciences, 2026)
Students’ low interest in learning English remains a persistent challenge in elementary education, as conventional teaching methods often fail to actively engage young learners. This study investigates the effect of Articulate Storyline 3 media on fifth-grade elementary school students' interest in learning English at SDN Rancatungku 01. A pre-experimental one group pre-test post-test design was employed for its practicality within a single intact classroom, although the absence of a control group means external influences such as repeated testing cannot be fully ruled out. The 32 fifth-grade students were selected through total sampling and given two treatment sessions using Articulate Storyline 3. A 10-item four-point Likert-scale questionnaire measuring four indicators, attention, participation, enthusiasm, and curiosity, was administered before and after treatment and analyzed using the Shapiro-Wilk test and Paired Samples T-Test via jamovi. Results confirmed normal data distribution and a statistically significant difference (p <.001), with the mean score increasing from 29.3 to 32.6, and 93.75% of students (30 of 32) showing improvement. The effect size Cohen’s d = -1.28 indicates the improvement is substantial enough to be practically meaningful for classroom practice. Thus, Articulate Storyline 3 media is effective in enhancing fifth-grade elementary school students’ interest in learning English.